Pengaruh Kompensasi, Motivasi Dan Beban Kerja Terhadap Kinerja Karyawan Di Kecamatan Ciracas - Alifia Meidyasti; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the influence of compensation, motivation and workload on employee performance. Employee performance is an important factor in achieving organizational goals. Research was conducted using survey methods and primary data collection through questionnaires distributed to employees at various levels in the organization. The data analysis technique used in this research uses SEM PLS which is calculated using Smart PLS 4.0 software. Data will be collected through a questionnaire with 18 questions and the sample in this study is 80 people, and will be measured using a Likert scale, with a score of one to five. The data analysis methods used in this research include measurement model analysis, structural model analysis, and direct influence hypothesis testing. The results of this research show that compensation has a significant and positive influence on employee performance, motivation also has a significant and positive influence on employee performance, and workload also has a significant and positive influence on employee performance. This research has important implications for human resource management in designing appropriate compensation policies, creating a motivating work environment, and managing employee workload wisely. By paying attention to these factors, companies or organizations can improve employee performance and achieve sustainable competitive advantage.